Adolescent exposure to a solid high-fat, high-sugar 'cafeteria' diet leads to more pronounced changes in metabolic measures and gut microbiome composition than liquid sugar in female rats. (1st May 2022) - Kendig, Michael D.; Hasebe, Kyoko; McCague, Róisín; Lee, Frances; Leigh, Sarah-Jane; Arnold, Ria; Morris, Margaret J.
Abstract: Adolescence is a dynamic developmental period where unhealthy solid foods and sugar-sweetened beverages are routinely consumed. Regular consumption of solid 'junk' foods rich in fat and refined carbohydrate and sugar-sweetened beverages are independently associated with an increased risk of metabolic disease and altered gut microbiome composition. Here we used a validated rat model to determine the effects of a solid 'cafeteria' diet high in fat and sugar (Caf) and 10% liquid sucrose solution (Suc) on food intake, metabolic measures and gut microbiome composition. Sixty adolescent female Sprague-Dawley rats were fed standard chow with or without continuous access to Caf diet and/or Suc for 13 weeks ( n  = 15). Exposure to cafeteria diet and liquid sucrose each increased body weight gain and adiposity, with no synergistic effects. Gut microbiome alpha and beta diversity parameters were more strongly affected by exposure to Caf diet than access to liquid Suc. Nonetheless, providing liquid sucrose to rats fed chow altered gut microbiome beta diversity and significantly enriched the abundance of five taxa from order Clostridiales . By contrast, in the two groups fed Caf, Suc did not alter beta diversity, with few differentially abundant taxa between Caf and Caf + Suc groups. In sum, liquid sucrose and solid cafeteria diet exerted largely independent effects on metabolic and gut microbiome measures. Interventions targeting either solid junk foods or sugary beverages are likely to reduce diet-related disease burden.